Pulmonary function in asbestos cement workers: a dose-response study. - Finkelstein, M (1986)
This study has found that residence time weighted exposure (asbestos dose) may be used to model the risk and extent of pulmonary function abnormalities in a cohort of asbestos cement workers. This parameter, which incorporates both exposure concentration and latency, had previously proved useful for modelling the risk of radiographic abnormalities in this cohort. Asbestos dose and smoking were independent and additive contributors to decreased pulmonary function. It was also found that lung function results could be used as surrogates for dose in the assessment of mortality risk in this cohort.